2019
DOI: 10.1007/s13205-019-1780-y
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of liver transcriptome from high- and low-intramuscular fat Chaohu ducks provided additional candidate genes for lipid selection

Abstract: The meat quality of ducks is closely related to the intramuscular fat (IMF) content. This study explored the candidate regulatory genes of IMF formation and lipid deposition in Chaohu ducks. The IMF of breast muscle in 100 ducks was determined and statistically analysed by normal distribution test. Duck liver samples with high IMF (CH, n = 3) and low IMF (CL, n = 3) were selected for transcriptome analysis by RNA sequencing (RNA-Seq). The IMF was in accordance with normal distribution (T = 0.001, P = 0.999). T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 49 publications
(31 reference statements)
0
4
0
Order By: Relevance
“…The results showed that the heritability of IMP at seven days post-mortem decreased from 0.32 to 0.08 when the NT5E genotype was included in the model. Similarly, NT5E , which is involved in the biological process of lipid deposition, has been identified as a candidate gene for selecting markers to control IMF formation in Chaohu ducks [ 70 ]. In this study, we identified 22 QTLs, including those related to meat quality, such as marbling (ID = 38049), muscle movement percentage (ID = 38073), and drip loss (ID = 21947,), based on CNVs located in the NT5E gene and the QTL database in control pigs.…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that the heritability of IMP at seven days post-mortem decreased from 0.32 to 0.08 when the NT5E genotype was included in the model. Similarly, NT5E , which is involved in the biological process of lipid deposition, has been identified as a candidate gene for selecting markers to control IMF formation in Chaohu ducks [ 70 ]. In this study, we identified 22 QTLs, including those related to meat quality, such as marbling (ID = 38049), muscle movement percentage (ID = 38073), and drip loss (ID = 21947,), based on CNVs located in the NT5E gene and the QTL database in control pigs.…”
Section: Discussionmentioning
confidence: 99%
“…GNAS plays multiple important roles in cell fate determination and differentiation during osteogenic differentiation [40]. NDUFA4L2 is considered to be a gene related to meat quality [41], and PPP1R3C is considered to be a candidate gene for intramuscular fat deposition in ducks [42].…”
Section: Discussionmentioning
confidence: 99%
“…KPNA7 (Karyopherin subunit alpha 7) which functions as a receptor for oocyte-specific protein that are important for oocyte and embryonic development 29 . HSD17B2 (Hydroxysteroid 17-beta dehydrogenase 2) a key regulator of steroid hormone metabolism 30 . LHX9 (LIM homeobox 9), which plays a key role in female reproductive tract development 31 .…”
Section: Discussionmentioning
confidence: 99%